BN-doped photo-thermal super-hydrophobic coating on surface of aluminum alloy and preparation method thereof
By preparing BN doped photothermal ultraspical coating on the surface of aluminum alloy, the problem of easy consumption of superhydrophobic coating is solved, and long-lasting superhydrophobic properties and efficient photothermal conversion are achieved, and the self-repair ability and environmental adaptability of the coating are improved.
Patent Information
- Application Number
- CN202510380455.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-28
- Publication Date
- 2025-07-01
AI Technical Summary
The existing superhydrophobic coatings are easily consumed, resulting in reduced superhydrophobic performance, and a single deicing method, making it difficult to meet the various application needs in different scenarios.
Using the preparation method of BN doped photothermal supersparing coating on the surface of aluminum alloy, the photothermal self-healing superhydrophobic coating was prepared by preparing mesoporous iron tetraoxide nanoparticles, coated titanium dioxide, and polydopamine functionalized boron nitride nanosheets, and TiO2@Fe3O4/BNNSs-PDA was synthesized to construct a photothermal self-healing superhydrophobic coating.
It realizes the long-lasting superhydrophobic properties of the coating and efficient photothermal conversion, enhances the self-healing ability of the coating, and broadens the application prospects in the fields of self-cleaning, corrosion resistance, ice protection, anti-fouling, etc.
Smart Images

Figure CN120230452A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of metal coating preparation methods, specifically relates to a preparation method of a BN-doped photothermal superhydrophobic coating on the surface of aluminum alloy, and also relates to a coating prepared by this preparation method. Background Art
[0002] At lower temperatures, the phenomenon of surface icing on high-voltage transmission lines can easily lead to frequent line breaks, greatly affecting the safe operation of the power system. Large-area icing will increase the mechanical burden on the poles and towers, and easily cause the poles and towers to break due to overloading. In response to this problem, superhydrophobic surfaces are currently the most widely studied and applied de-icing technologies, which can achieve various beneficial effects such as self-cleaning, anti-corrosion, and anti-icing. However, traditional superhydrophobic surfaces have problems such as easy consumption of low-surface-energy materials, poor abrasion resistance of micro-nano structures, and low passive de-icing efficiency, and it is difficult to maintain durable performance in complex environments.
[0003] Due to its unique properties, magnetite has been widely used in the field of photothermal conversion, but its own photothermal conversion efficiency still cannot fully meet the actual needs. By preparing mesoporous magnetite composites, the photothermal conversion efficiency and the loading amount of low-surface-energy materials can be significantly improved, realizing efficient photothermal driving, and then promoting the shape memory effect of epoxy resin. By utilizing the synergistic effect of nano-containers storing low-surface-energy materials and epoxy resin, durable superhydrophobic properties can be obtained. As a reusable natural resource, solar energy combines passive de-icing with active de-icing, which can effectively cooperate with superhydrophobic surfaces to improve the de-icing effect. Therefore, it is very necessary to prepare a superhydrophobic coating with high photothermal and self-healing properties.
[0004] Chinese Patent "Superhydrophobic Coating and Its Preparation Method, Superhydrophobic Coating and Application" (Application No.: CN202411446861.2, Authorization No.: CN119081529A, Publication Date: 2024.10.16) discloses a superhydrophobic coating and its preparation method, superhydrophobic coating and application. The superhydrophobic coating prepared by the superhydrophobic coating can achieve self-warning and self-healing of damage. However, the coating has a single de-icing method and unsatisfactory effects, and it is difficult to meet the multiple application requirements in different scenarios. Summary of the Invention
[0005] The purpose of the present invention is to provide a preparation method of a BN-doped photothermal superhydrophobic coating on the surface of aluminum alloy, which solves the problem that the superhydrophobic performance of the coating in the prior art is reduced due to easy consumption.
[0006] Another purpose of the present invention is to provide a coating prepared by using the preparation method of the BN-doped photothermal superhydrophobic coating on the surface of aluminum alloy.
[0007] The technical solution adopted by the present invention is a method for preparing a BN-doped photothermal superhydrophobic coating on the surface of aluminum alloy, which is specifically implemented according to the following steps:
[0008] Step 1, mesoporous iron oxide nanoparticles;
[0009] Step 2, titanium dioxide-coated mesoporous iron oxide nanoparticles;
[0010] Step 3, polydopamine-functionalized boron nitride nanosheets;
[0011] Step 4, synthesize TiO2@Fe3O4 / BNNSs-PDA;
[0012] Step 5, construct a photothermal self-healing superhydrophobic coating.
[0013] The characteristics of the present invention also lie in that
[0014] Step 1 is specifically as follows: Dissolve ferric chloride hexahydrate and citric acid with a mass ratio of 1:2 - 1:1 in ethylene glycol, heat and stir at 80°C - 120°C for 3h - 6h to form a gel, and then place it in a tube furnace. The temperature of the tube furnace is raised to 500°C at a rate of 5°C / min and calcined for 3h - 5h to obtain mesoporous iron oxide nanoparticles.
[0015] Step 2 is specifically as follows: Disperse the mesoporous iron oxide obtained in Step 1 in absolute ethanol, add tetrabutyl titanate and stir evenly, then carry out a high-temperature thermal reaction, let it stand and wash, and vacuum dry to obtain titanium dioxide-coated mesoporous iron oxide nanoparticles.
[0016] The dispersion liquid in Step 2 is composed of the following substances by mass percentage: mesoporous iron oxide nanoparticles are 1% - 2%, tetrabutyl titanate is 0.5% - 1%, and the rest is absolute ethanol, and the sum of the above components is 100%; the high-temperature thermal reaction temperature is 140°C - 160°C, and the reaction time is 12h - 15h; the vacuum drying temperature is 50°C - 80°C, and the drying time is 4h - 8h.
[0017] Step 3 is specifically as follows: Add tris(hydroxymethyl)aminomethane, dopamine hydrochloride, and BNNSs to deionized water in sequence, stir well to obtain a suspension, and then wash and filter to obtain BNNSs-PDA nanosheets; the suspension is composed of the following substances by mass percentage: tris(hydroxymethyl)aminomethane is 4% - 5%, dopamine hydrochloride is 4% - 5%, BNNSs is 20% - 25%, and the rest is deionized water, and the sum of the above components is 100%.
[0018] Step 4 specifically includes: successively adding a silane coupling agent, the TiO2@Fe3O4 prepared in Step 2, and the BNNSs-PDA nanosheets in Step 3 into a mixed solution composed of absolute ethanol and deionized water, heating and stirring, washing and drying to obtain TiO2@Fe3O4 / BNNSs-PDA.
[0019] The mixed solution in Step 4 is composed of the following substances by mass percentage: TiO2@Fe3O4 is 3%-5%, the silane coupling agent is 15%-30%, BNNSs-PDA is 3%-5%, and a mixed solvent composed of absolute ethanol and deionized water in an equal volume ratio is 60%-79%. The sum of the above components is 100%. The silane coupling agent is any one of γ-methacryloxypropyltrimethoxysilane and γ-aminopropyltriethoxysilane.
[0020] In Step 4, the heating temperature is 60°C - 80°C, the stirring speed is 500 rpm - 700 rpm, and the stirring time is 4 h - 6 h. The drying temperature is 60°C - 80°C, and the drying time is 6 h - 8 h.
[0021] Step 5 specifically includes: dissolving epoxy resin and polycaprolactone with a mass ratio of 1:2 - 2:1 into an ethyl acetate solution, adding the TiO2@Fe3O4 / BNNSs-PDA prepared in Step 4 to make a suspension, mixing with a curing agent at room temperature to obtain a coating, using a spray gun with a pressure of 0.25 MPa - 0.3 MPa, with a flow rate of 40 mL / min - 50 mL / min, a spraying distance of 10 cm - 20 cm, placing the substrate at an inclination of 30° - 45° during spraying, spraying on the metal surface, and then drying at a high temperature of 60°C - 80°C for 2 h - 3 h to obtain a photothermal and self-healing superhydrophobic coating.
[0022] Another technical solution adopted by the present invention is a coating prepared by a method for preparing a BN-doped photothermal superhydrophobic coating on the surface of an aluminum alloy.
[0023] The beneficial effects of the present invention are:
[0024] The method for preparing the BN-doped photothermal superhydrophobic coating on the surface of an aluminum alloy of the present invention modifies BNNSs with polydopamine, and uses the multi-functional groups of polydopamine to attach nano-scale modified TiO2@Fe3O4 to the surface, enabling the prepared composite material to have excellent photothermal conversion performance while providing a lasting superhydrophobic property. The excellent thermal conductivity of BNNSs enables the heat generated by photothermal conversion to be transferred to the epoxy resin, enhancing the shape memory effect and promoting the self-healing performance of the coating. Therefore, the coating not only reduces resource consumption but also improves the environmental adaptability, greatly broadening the application prospects in the fields of self-cleaning, anti-corrosion, anti-icing, anti-fouling, etc. Description of the Drawings
[0025] Figure 1 It is a schematic diagram of the morphology of EP-PCL-based TiO2@Fe3O4 / BNNSs-PDA prepared by the present invention. Specific embodiments
[0026] The present invention will be described in detail below in conjunction with specific embodiments and the accompanying drawings.
[0027] The preparation method of the BN-doped photothermal superhydrophobic coating on the aluminum alloy surface of the present invention is specifically implemented according to the following steps:
[0028] Step 1, mesoporous iron oxide nanoparticles;
[0029] Step 1 is specifically as follows: Dissolve ferric chloride hexahydrate and citric acid with a mass ratio of 1:2 - 1:1 in ethylene glycol, heat and stir at 80°C - 120°C for 3h - 6h to form a gel, and then place it in a tubular furnace. The temperature of the tubular furnace is raised to 500°C at a rate of 5°C / min and calcined for 3h - 5h to obtain mesoporous iron oxide nanoparticles;
[0030] Step 2, titanium dioxide-coated mesoporous iron oxide nanoparticles;
[0031] Step 2 is specifically as follows: Disperse the mesoporous Fe3O4 obtained in Step 1 in absolute ethanol, add tetrabutyl titanate and stir evenly, then carry out a high-temperature thermal reaction, wash after standing, and vacuum dry to obtain titanium dioxide-coated mesoporous iron oxide nanoparticles (TiO2@Fe3O4);
[0032] In Step 2, the dispersion is composed of the following substances by mass percentage: mesoporous iron oxide nanoparticles are 1% - 2%, tetrabutyl titanate is 0.5% - 1%, and the rest is absolute ethanol, and the sum of the above components is 100%; the high-temperature thermal reaction temperature is 140°C - 160°C, and the reaction time is 12h - 15h; the temperature of vacuum drying is 50°C - 80°C, and the drying time is 4h - 8h;
[0033] Step 3, polydopamine-functionalized boron nitride nanosheets;
[0034] Step 3 is specifically as follows: Add tris(hydroxymethyl)aminomethane, dopamine hydrochloride, and BNNSs to deionized water in sequence, stir well to obtain a suspension, and then wash and filter to obtain BNNSs-PDA nanosheets; the suspension is composed of the following substances by mass percentage: tris(hydroxymethyl)aminomethane is 4% - 5%, dopamine hydrochloride is 4% - 5%, BNNSs is 20% - 25%, and the rest is deionized water, and the sum of the above components is 100%;
[0035] Step 4, synthesize TiO2@Fe3O4 / BNNSs-PDA;
[0036] Step 4 specifically includes: successively adding a silane coupling agent, the TiO2@Fe3O4 prepared in Step 2, and the BNNSs-PDA nanosheets in Step 3 into a mixed solution composed of anhydrous ethanol and deionized water, heating and stirring, washing and drying to obtain TiO2@Fe3O4 / BNNSs-PDA;
[0037] The mixed solution in Step 4 is composed of the following substances by mass percentage: TiO2@Fe3O4 is 3% - 5%, the silane coupling agent is 15% - 30%, BNNSs-PDA is 3% - 5%, and a mixed solvent composed of anhydrous ethanol and deionized water with an equal volume ratio is 60% - 79%. The sum of the above components is 100%; the silane coupling agent is any one of γ-methacryloxypropyltrimethoxysilane (KH570) and γ-aminopropyltriethoxysilane (KH550);
[0038] In Step 4, the heating temperature is 60°C - 80°C, the stirring speed is 500 rpm - 700 rpm, and the stirring time is 4 h - 6 h; the drying temperature is 60°C - 80°C, and the drying time is 6 h - 8 h;
[0039] Step 5, constructing a photothermal self-healing superhydrophobic coating;
[0040] Step 5 specifically includes: dissolving epoxy resin and polycaprolactone with a mass ratio of 1:2 - 2:1 into an ethyl acetate solution, adding the TiO2@Fe3O4 / BNNSs-PDA prepared in Step 4 to make a suspension, mixing with a curing agent at room temperature to obtain a coating, using a spray gun with a pressure of 0.25 MPa - 0.3 MPa, with a flow rate of 40 mL / min - 50 mL / min, a spraying distance of 10 cm - 20 cm, placing the substrate at an inclination of 30° - 45° during spraying, spraying on the metal surface, and then drying at a high temperature of 60°C - 80°C for 2 h - 3 h to obtain a photothermal and self-healing superhydrophobic coating.
[0041] In the present invention, nano-sized mesoporous iron tetroxide is prepared. By virtue of its excellent high specific surface area characteristics, a larger area for grafting silane coupling agent is achieved, thereby effectively regulating the surface chemical properties and enhancing the binding force with other materials. TiO2 has strong absorption in the ultraviolet region, and Fe3O4 has certain absorption in the visible and near-infrared regions. After the two materials form a heterojunction, the absorption spectra complement each other, enabling more efficient utilization of the energy of sunlight and improving the photothermal conversion performance. BNNSs have excellent thermal conductivity and can form an efficient thermal conduction pathway and network. By utilizing the good adhesion and multi-functional group characteristics of PDA, nano-sized modified TiO2@Fe3O4 is attached to the surface of BNNSs, enhancing its compatibility with the polymer matrix and achieving a good dispersion state, comprehensively improving the comprehensive performance of the composite material. By introducing a rough structure and silane coupling agent, the surface energy is reduced and the hydrophobicity of the material is enhanced. Epoxy resin has a relatively high modulus and hardness, which can endow the composite material with excellent structural strength; polycaprolactone has good flexibility and processing performance, which can improve the toughness of the composite material. Adjusting the proportion of epoxy resin and polycaprolactone can optimize the mechanical properties and thermal stability of the composite material. The composite material integrating polydopamine, TiO2@Fe3O4 and BNNSs can not only quickly conduct heat to the entire coating after absorbing light energy, realizing the integration of photothermal and thermal conduction, but also promote the self-healing ability of the coating through the synergistic effect of the three, making the coating have better durability.
[0042] Example 1
[0043] The preparation method of the BN-doped photothermal superhydrophobic coating on the aluminum alloy surface of the present invention is specifically as follows:
[0044] 4 g of ferric chloride hexahydrate and citric acid with a mass ratio of 1:2 are successively dissolved in 50 mL of ethylene glycol, heated to 80 °C and stirred for 3 h to form a gel. When the gel is preliminarily dried, it is placed in a tubular furnace. Under a nitrogen atmosphere, it is heated from room temperature to 500 °C at a rate of 5 °C / min and reacted for 3 h. After cooling to room temperature, mesoporous Fe3O4 is obtained.
[0045] According to the mass percentage: mesoporous iron tetroxide nanoparticles are 1%, tetrabutyl titanate is 0.5%, and the rest is anhydrous ethanol. Stir evenly to prepare a dispersion; put the container containing the dispersion into a container filled with deionized water and react at a high temperature of 140 °C for 12 h; after the reaction, let it stand, wash it 3 times with anhydrous ethanol and deionized water respectively, and then dry it in vacuum at 50 °C for 4 h to obtain TiO2@Fe3O4.
[0046] The mixed solution was prepared with a mass percentage of 4% tris(hydroxymethyl)aminomethane, 4% dopamine hydrochloride, 20% BNNSs, and the rest being deionized water, and stirred for 8 h. The obtained precipitate was washed three times each with absolute ethanol and deionized water, and then vacuum filtered to obtain BNNSs-PDA nanosheets.
[0047] TiO2@Fe3O4, BNNSs-PDA, KH570, absolute ethanol and deionized water were mixed according to the mass percentage, with TiO2@Fe3O4 being 3%, KH570 being 15%, BNNSs-PDA being 3%, and the rest being absolute ethanol and deionized water with an equal volume ratio. They were stirred at 500 rpm for 4 h in a 60 °C water bath to obtain a stable suspension, filtered and alternately washed three times with ethanol and deionized water, and then dried at 60 °C for 6 h to obtain TiO2@Fe3O4 / BNNSs-PDA.
[0048] 10 g of epoxy resin and polycaprolactone with a mass ratio of 1:2 were dissolved in 20 mL of ethyl acetate solvent, then 6 g of TiO2@Fe3O4 / BNNSs-PDA was added and vigorously stirred at a speed of not less than 1000 r / min for 0.5 h to obtain a suspension. 5 g of polyamide was added 10 min before spraying, and after dispersion, an EP-PCL-based TiO2@Fe3O4 / BNNSs-PDA coating was formed.
[0049] The coating was sprayed on the metal surface using a spray gun, with the spray gun pressure set at 0.25 MPa, the flow rate at 40 mL / min, the spraying distance at 10 cm, and the substrate tilted at 30° during spraying. It was dried at 60 °C for 2 h to obtain a photothermal self-healing superhydrophobic coating.
[0050] Example 2
[0051] The preparation method of the BN-doped photothermal superhydrophobic coating on the aluminum alloy surface of the present invention is specifically as follows:
[0052] 4 g of ferric chloride hexahydrate and citric acid with a mass ratio of 1:1 were successively dissolved in 50 mL of ethylene glycol, heated to 120 °C and stirred for 6 h to form a gel. When the gel was preliminarily dried, it was placed in a tubular furnace. Under a nitrogen atmosphere, it was heated from room temperature to 500 °C at a rate of 5 °C / min and reacted for 5 h. After cooling to room temperature, mesoporous Fe3O4 was obtained.
[0053] According to the mass percentage: mesoporous iron oxide nanoparticles were 2%, tetrabutyl titanate was 1%, and the rest was absolute ethanol. They were stirred evenly to prepare a dispersion. The container containing the dispersion was placed in a container filled with deionized water and reacted at a high temperature of 160 °C for 15 h. After the reaction, it was left to stand, washed five times each with absolute ethanol and deionized water, and then vacuum dried at 80 °C for 8 h to obtain TiO2@Fe3O4.
[0054] The mixed solution was prepared with a mass percentage of 5% tris(hydroxymethyl)aminomethane, 5% dopamine hydrochloride, 25% BNNSs, and the rest being deionized water, and stirred for 12 h. The resulting precipitate was washed 5 times each with absolute ethanol and deionized water, and then vacuum filtered to obtain BNNSs-PDA nanosheets.
[0055] TiO2@Fe3O4, BNNSs-PDA, KH550, absolute ethanol and deionized water were mixed according to the mass percentage, with TiO2@Fe3O4 being 5%, KH550 being 30%, BNNSs-PDA being 5%, and the rest being absolute ethanol and deionized water in an equal volume ratio. They were stirred at 700 rpm for 6 h in an 80 °C water bath to obtain a stable suspension, filtered and alternately washed 5 times with ethanol and deionized water, and dried at 80 °C for 8 h to obtain TiO2@Fe3O4 / BNNSs-PDA.
[0056] 10 g of epoxy resin and polycaprolactone with a mass ratio of 2:1 were dissolved in 20 mL of ethyl acetate solvent, then 6 g of TiO2@Fe3O4 / BNNSs-PDA was added and vigorously stirred at a speed of not less than 1000 r / min for 1 h to obtain a suspension. 5 g of tertiary amine was added 10 min before spraying, and after dispersion, an EP-PCL-based TiO2@Fe3O4 / BNNSs-PDA coating was formed.
[0057] The coating was sprayed on the metal surface using a spray gun, with the spray gun pressure set at 0.3 MPa, the flow rate at 50 mL / min, the spraying distance at 20 cm, the substrate placed at an inclination of 45° during spraying, and dried at 80 °C for 3 h to obtain a photothermal self-healing superhydrophobic coating.
[0058] Example 3
[0059] The preparation method of the BN-doped photothermal superhydrophobic coating on the aluminum alloy surface of the present invention is specifically as follows:
[0060] 4 g of ferric chloride hexahydrate and citric acid with a mass ratio of 1:2 were successively dissolved in 50 mL of ethylene glycol, heated to 120 °C and stirred for 6 h to form a gel. When the gel was preliminarily dried, it was placed in a tubular furnace, and under a nitrogen atmosphere, heated from room temperature to 500 °C at a rate of 5 °C / min and reacted for 5 h. After cooling to room temperature, mesoporous Fe3O4 was obtained.
[0061] According to the mass percentage: mesoporous iron oxide nanoparticles were 1%, tetrabutyl titanate was 0.5%, and the rest was absolute ethanol. They were stirred evenly to prepare a dispersion. The container containing the dispersion was placed in a container filled with deionized water and reacted at a high temperature of 150 °C for 12 h. After the reaction, it was allowed to stand, washed 3 times each with absolute ethanol and deionized water, and then vacuum dried at 80 °C for 8 h to obtain TiO2@Fe3O4.
[0062] The mixed solution was prepared with a mass percentage of 5% tris(hydroxymethyl)aminomethane, 5% dopamine hydrochloride, 20% BNNSs, and the rest being deionized water, and stirred for 12 h. The resulting precipitate was washed three times each with absolute ethanol and deionized water, and then vacuum filtered to obtain BNNSs-PDA nanosheets.
[0063] TiO2@Fe3O4, BNNSs-PDA, KH570, absolute ethanol and deionized water were mixed according to the mass percentage, with TiO2@Fe3O4 being 3%, KH570 being 30%, BNNSs-PDA being 5%, and the rest being absolute ethanol and deionized water in an equal volume ratio. They were stirred at 700 rpm for 4 h in an 80 °C water bath to obtain a stable suspension, filtered and washed alternately three times with ethanol and deionized water, and dried at 80 °C for 8 h to obtain TiO2@Fe3O4 / BNNSs-PDA.
[0064] 10 g of epoxy resin and polycaprolactone with a mass ratio of 2:1 were dissolved in 20 mL of ethyl acetate solvent, then 6 g of TiO2@Fe3O4 / BNNSs-PDA was added and stirred vigorously at a speed of not less than 1000 r / min for 0.5 h to obtain a suspension. 5 g of polyamide was added 10 min before spraying, and after dispersion, an EP-PCL-based TiO2@Fe3O4 / BNNSs-PDA coating was formed.
[0065] The coating was sprayed on the metal surface using a spray gun, with the spray gun pressure set at 0.3 MPa, the flow rate at 40 mL / min, the spraying distance at 10 cm, and the substrate tilted at 30° during spraying. It was dried at 80 °C for 2 h to obtain a photothermal self-healing superhydrophobic coating.
[0066] Example 4
[0067] The preparation method of the BN-doped photothermal superhydrophobic coating on the aluminum alloy surface of the present invention is specifically as follows:
[0068] 4 g of ferric chloride hexahydrate and citric acid with a mass ratio of 1:1 were successively dissolved in 50 mL of ethylene glycol, heated to 120 °C and stirred for 6 h to form a gel. When the gel was preliminarily dried, it was placed in a tubular furnace, and under a nitrogen atmosphere, it was heated from room temperature to 500 °C at a rate of 5 °C / min and reacted for 5 h. After cooling to room temperature, mesoporous Fe3O4 was obtained.
[0069] According to the mass percentage: mesoporous iron oxide nanoparticles were 1%, tetrabutyl titanate was 1%, and the rest was absolute ethanol. They were stirred evenly to prepare a dispersion. The container containing the dispersion was placed in a container filled with deionized water and reacted at a high temperature of 150 °C for 12 h. After the reaction ended, it was allowed to stand, washed three times each with absolute ethanol and deionized water, and then vacuum dried at 80 °C for 8 h to obtain TiO2@Fe3O4.
[0070] The mixed solution was prepared with a mass percentage of 5% tris(hydroxymethyl)aminomethane, 5% dopamine hydrochloride, 20% BNNSs, and the rest being deionized water. It was stirred for 12 h. The resulting precipitate was washed three times each with absolute ethanol and deionized water, and then vacuum filtered to obtain BNNSs-PDA nanosheets.
[0071] TiO2@Fe3O4, BNNSs-PDA, KH570, absolute ethanol, and deionized water were mixed according to the mass percentage: 5% TiO2@Fe3O4, 25% KH570, 5% BNNSs-PDA, and the rest being absolute ethanol and deionized water in an equal volume ratio. They were stirred at 500 rpm for 4 h in an 80 °C water bath to obtain a stable suspension. After filtration, it was alternately washed three times with ethanol and deionized water, and then dried at 80 °C for 6 h to obtain TiO2@Fe3O4 / BNNSs-PDA.
[0072] 10 g of epoxy resin and polycaprolactone with a mass ratio of 1:1 were dissolved in 20 mL of ethyl acetate solvent, and then 6 g of TiO2@Fe3O4 / BNNSs-PDA was added and vigorously stirred at a speed of not less than 1000 r / min for 0.5 h to obtain a suspension. 5 g of polyamide was added 10 min before spraying, and after dispersion, an EP-PCL-based TiO2@Fe3O4 / BNNSs-PDA coating was formed.
[0073] The coating was sprayed on the metal surface using a spray gun, with the spray gun pressure set at 0.3 MPa, the flow rate at 40 mL / min, the spraying distance at 10 cm, and the substrate tilted at 30° during spraying. It was dried at 80 °C for 2 h to obtain a photothermal self-healing superhydrophobic coating, as Figure 1 shown.
[0074] Example 5
[0075] 4 g of ferric chloride hexahydrate and citric acid with a mass ratio of 1:1 were successively dissolved in 50 mL of ethylene glycol, heated and stirred at 90 °C for 4 h to form a gel. When the gel was preliminarily dried, it was placed in a tubular furnace. Under a nitrogen atmosphere, it was heated from room temperature to 500 °C at a rate of 5 °C / min and reacted for 3 h. After cooling to room temperature, mesoporous Fe3O4 was obtained.
[0076] According to the mass percentage: 1% mesoporous iron oxide nanoparticles, 0.5% tetrabutyl titanate, and the rest being absolute ethanol, they were stirred evenly to prepare a dispersion. The container containing the dispersion was placed in a container filled with deionized water and reacted at a high temperature of 150 °C for 12 h. After the reaction ended, it was allowed to stand, washed three times each with absolute ethanol and deionized water, and then vacuum dried at 80 °C for 7 h to obtain TiO2@Fe3O4.
[0077] The mixed solution was prepared with a mass percentage of 5% tris(hydroxymethyl)aminomethane, 5% dopamine hydrochloride, 20% BNNSs, and the rest being deionized water. It was stirred for 12 h. The obtained precipitate was washed 3 times each with absolute ethanol and deionized water, and then vacuum filtered to obtain BNNSs-PDA nanosheets.
[0078] TiO2@Fe3O4, BNNSs-PDA, KH570, absolute ethanol and deionized water were mixed according to the mass percentage, with TiO2@Fe3O4 being 5%, KH570 being 30%, BNNSs-PDA being 3%, and the rest being absolute ethanol and deionized water in an equal volume ratio. They were stirred at 500 rpm for 4 h in an 80 °C water bath to obtain a stable suspension. After filtration, it was alternately washed 3 times with ethanol and deionized water, and then dried at 80 °C for 6 h to obtain TiO2@Fe3O4 / BNNSs-PDA.
[0079] 10 g of epoxy resin and polycaprolactone with a mass ratio of 1:1 were dissolved in 20 mL of ethyl acetate solvent, and then 6 g of TiO2@Fe3O4 / BNNSs-PDA was added and vigorously stirred at a speed of not less than 1000 r / min for 0.5 h to obtain a suspension. 5 g of polyamide was added 10 min before spraying, and after dispersion, an EP-PCL-based TiO2@Fe3O4 / BNNSs-PDA coating was formed.
[0080] The coating was sprayed on the metal surface using a spray gun, with the spray gun pressure set at 0.3 MPa, the flow rate at 45 mL / min, the spraying distance at 15 cm, and the substrate tilted at 40° during spraying. It was dried at 80 °C for 2 h to obtain a photothermal self-healing superhydrophobic coating.
[0081] Example 6
[0082] 4 g of ferric chloride hexahydrate and citric acid with a mass ratio of 1:1 were successively dissolved in 50 mL of ethylene glycol, heated and stirred at 110 °C for 5 h to form a gel. When the gel was preliminarily dried, it was placed in a tubular furnace. Under a nitrogen atmosphere, it was heated from room temperature to 500 °C at a rate of 5 °C / min and reacted for 4 h. After cooling to room temperature, mesoporous Fe3O4 was obtained.
[0083] According to the mass percentage: mesoporous iron oxide nanoparticles were 1.5%, tetrabutyl titanate was 1%, and the rest was absolute ethanol. They were stirred evenly to prepare a dispersion. The container containing the dispersion was placed in a container filled with deionized water and reacted at a high temperature of 150 °C for 13 h. After the reaction ended, it was allowed to stand, washed 3 times each with absolute ethanol and deionized water, and then vacuum dried at 75 °C for 5 h to obtain TiO2@Fe3O4.
[0084] The mixed solution was prepared with a mass percentage of 5% tris(hydroxymethyl)aminomethane, 5% dopamine hydrochloride, 23% BNNSs, and the rest being deionized water. It was stirred for 12 h. The obtained precipitate was washed three times each with absolute ethanol and deionized water, and then vacuum filtered to obtain BNNSs-PDA nanosheets.
[0085] TiO2@Fe3O4, BNNSs-PDA, KH570, absolute ethanol and deionized water were mixed according to the mass percentage. TiO2@Fe3O4 was 5%, KH570 was 25%, BNNSs-PDA was 5%, and the rest were absolute ethanol and deionized water with an equal volume ratio. It was stirred at 500 rpm for 4 h in an 80 °C water bath to obtain a stable suspension. It was filtered and alternately washed three times with ethanol and deionized water, and then dried at 80 °C for 6 h to obtain TiO2@Fe3O4 / BNNSs-PDA.
[0086] 10 g of epoxy resin and polycaprolactone with a mass ratio of 1:1 were dissolved in 20 mL of ethyl acetate solvent, then 6 g of TiO2@Fe3O4 / BNNSs-PDA was added and vigorously stirred at a speed of not less than 1000 r / min for 0.5 h to obtain a suspension. 5 g of polyamide was added 10 min before spraying, and after dispersion, an EP-PCL-based TiO2@Fe3O4 / BNNSs-PDA coating was formed.
[0087] The coating was sprayed on the metal surface using a spray gun. The spray gun pressure was set at 0.3 MPa, the flow rate was 45 mL / min, the spraying distance was 20 cm, and the substrate was placed at an inclination of 45° during spraying. It was dried at 80 °C for 2 h to obtain a photothermal self-healing superhydrophobic coating.
[0088] Table 1 below shows the comparison of the water contact angle, photothermal equilibrium temperature, ice melting time, and self-healing time of the coating in Example 4 and the coatings in Comparative Examples 1-3. Comparative Example 1 has a mass ratio of ferric chloride hexahydrate to citric acid of 2:1 in Step 1 of Example 4. Comparative Example 2 has an addition amount of mesoporous iron oxide nanoparticles of 0.2% in Step 2 of Example 4. Comparative Example 3 has an addition amount of BNNSs of 5% in Step 3 of Example 4. The other step parameters are the same as those in Example 4. It can be seen from Table 1 that the coating in Example 4 has the best comprehensive performance. By changing the mass ratio of epoxy resin to polycaprolactone and adjusting the proportional relationship between epoxy resin and polycaprolactone, the mechanical properties and thermal stability of the composite material can be optimized, which helps to adjust the shape memory effect of the matrix. The synergistic photothermal conversion ability between the polydopamine and the titanium dioxide-coated iron oxide composite improves the ice melting performance of the coating under light irradiation and reduces the ice melting time. And by modifying BNNSs with polydopamine and attaching nanoscale modified TiO2@Fe3O4 on the surface, not only does the prepared composite material achieve good heat conduction performance, but also a micro-nano structure is constructed, significantly improving the superhydrophobic performance. The excellent heat conduction performance of BNNSs enables heat to be transferred to the epoxy resin, further enhancing the shape memory effect and promoting the self-healing performance. Therefore, the comprehensive performance is the best.
[0089] Table 1
[0090]
[0091] In this invention, a superhydrophobic coating with high photothermal and self-healing properties was prepared by the sol-gel method. By modifying BNNSs with PDA and using the multi-functional groups of PDA to attach nanoscale modified TiO2@Fe3O4 on the surface, the prepared composite material has excellent photothermal conversion performance and provides durable superhydrophobic performance. The excellent heat conduction performance of BNNSs enables the heat generated by photothermal conversion to be transferred to the epoxy resin, enhancing the shape memory effect and promoting the self-healing performance. This coating not only reduces resource consumption but also improves the environmental adaptability of the superhydrophobic coating, greatly broadening the application prospects.
Claims
1. A method for preparing a BN-doped photothermal superphobic coating on an aluminum alloy surface, characterized in that: Follow the steps below to implement it: Step 1, mesoporous ferroferric oxide nanoparticles; Step 2, titanium dioxide coated mesoporous ferroferric oxide nanoparticles; Step 3, functionalizing boron nitride nanosheets with polydopamine; Step 4, synthesizing TiO2@Fe3O4 / BNNSs-PDA; Step 5, construct a photothermal self-repairing super-hydrophobic coating.
2. The method for preparing the BN-doped photothermal superphobic coating on the surface of aluminum alloy according to claim 1, characterized in that: The step 1 is specifically as follows: dissolving ferric chloride hexahydrate and citric acid in a mass ratio of 1:2-1:1 in ethylene glycol, heating and stirring at 80°C-120°C for 3h-6h to form a gel, and then placing the gel in a tubular furnace, heating the temperature of the tubular furnace to 500°C at a rate of 5°C / min, and calcining the mixture for 3h-5h to obtain ferrosoferric oxide nanoparticles with a mesoporous structure.
3. The method for preparing the BN-doped photothermal superphobic coating on the surface of aluminum alloy according to claim 1, characterized in that: The step 2 specifically comprises: dispersing the mesoporous ferroferric oxide of step 1 in anhydrous ethanol, adding tetrabutyl titanate, stirring evenly, and then performing a high-temperature thermal reaction, standing and then washing, and vacuum drying to obtain titanium dioxide-coated mesoporous ferroferric oxide nanoparticles.
4. The method for preparing the BN-doped photothermal superphobic coating on the surface of aluminum alloy according to claim 3, characterized in that: The dispersion in step 2 is composed of the following substances in percentage by mass: 1%-2% of mesoporous ferrosoferric oxide nanoparticles, 0.5%-1% of tetrabutyl titanate, and the rest are anhydrous ethanol, the sum of the above components being 100%; the high-temperature thermal reaction temperature is 140°C-160°C, and the reaction time is 12h-15h; the vacuum drying temperature is 50°C-80°C, and the drying time is 4h-8h.
5. The method for preparing the BN-doped photothermal superphobic coating on the surface of aluminum alloy according to claim 1, characterized in that: The step 3 is specifically as follows: tris(hydroxymethyl)aminomethane, dopamine hydrochloride and BNNSs are added to deionized water in sequence, stirred sufficiently to obtain a suspension, and then washed and filtered to obtain BNNSs-PDA nanosheets; the suspension is composed of the following substances by mass percentage: tris(hydroxymethyl)aminomethane is 4%-5%, dopamine hydrochloride is 4%-5%, BNNSs is 20%-25%, and the rest is deionized water, and the sum of the above components is 100%.
6. The method for preparing the BN-doped photothermal superphobic coating on the surface of aluminum alloy according to claim 1, characterized in that: The step 4 is specifically as follows: sequentially adding the silane coupling agent, the TiO2@Fe3O4 prepared in step 2 and the BNNSs-PDA nanosheets in step 3 into a mixed solution consisting of anhydrous ethanol and deionized water, heating and stirring, washing and drying to obtain TiO2@Fe3O4 / BNNSs-PDA.
7. The method for preparing the BN-doped photothermal superphobic coating on the surface of aluminum alloy according to claim 6, characterized in that: The mixed solution of step 4 is composed of the following substances in mass percentage: TiO2@Fe3O4 is 3%-5%, silane coupling agent is 15%-30%, BNNSs-PDA is 3%-5%, and a mixed solvent composed of anhydrous ethanol and deionized water in equal volume ratios is 60%-79%, and the total of the above components is 100%; the silane coupling agent is any one of γ-methacryloxypropyltrimethoxysilane and γ-aminopropyltriethoxysilane.
8. The method for preparing the BN-doped photothermal superphobic coating on the surface of aluminum alloy according to claim 6, characterized in that: In step 4, the heating temperature is 60° C.-80° C., the stirring speed is 500 rpm-700 rpm, and the stirring time is 4 h-6 h; the drying temperature is 60° C.-80° C., and the drying time is 6 h-8 h.
9. The method for preparing a BN-doped photothermal superphobic coating on an aluminum alloy surface according to claim 1, characterized in that: The step 5 is specifically as follows: after dissolving epoxy resin and polycaprolactone in a mass ratio of 1:2-2:1 into an ethyl acetate solution, the TiO2@Fe3O4 / BNNSs-PDA prepared in step 4 is added to make a suspension, and mixed with a curing agent of any one of polyamide and tertiary amine at room temperature to obtain a coating, using a spray gun with a pressure of 0.25MPa-0.3Mpa, a flow rate of 40mL / min-50mL / min, a spraying distance of 10cm-20cm, and the substrate is tilted at 30°-45° during spraying, spraying on the metal surface, and then drying at a temperature of 60°C-80°C for 2h-3h to obtain a photothermal, self-healing super hydrophobic coating.
10. A coating prepared according to the method for preparing a BN-doped photothermal superphobic coating on an aluminum alloy surface according to any one of claims 1 to 9.
Citation Information
Patent Citations
Super-hydrophobic coating, preparation method thereof, super-hydrophobic coating and application
CN119081529A